Cyclin D1 depletion induces DNA damage in mantle cell lymphoma lines. Issue 3 (4th March 2017) - Mohanty, Suchismita; Mohanty, Atish; Sandoval, Natalie; Tran, Thai; Bedell, Victoria; Wu, Jun; Scuto, Anna; Murata-Collins, Joyce; Weisenburger, Dennis D.; Ngo, Vu N.
Abstract: Elevated cyclin D1 (CCND1) expression levels in mantle cell lymphoma (MCL) are associated with aggressive clinical manifestations related to chemoresistance, but little is known about how this important proto-oncogene contributes to the resistance of MCL. Here, we showed that RNA interference-mediated depletion of CCND1 increased caspase-3 activities and induced apoptosis in the human MCL lines UPN-1 and JEKO-1. In vitro and xenotransplant studies revealed that the toxic effect of CCND1 depletion in MCL cells was likely due to increase in histone H2AX phosphorylation, a DNA damage marker. DNA fiber analysis suggested deregulated replication initiation after CCND1 depletion as a potential cause of DNA damage. Finally, in contrast to depletion or inhibition of cyclin-dependent kinase 4, CCND1 depletion increased chemosensitivity of MCL cells to replication inhibitors hydroxyurea and cytarabine. Our findings have an important implication for CCND1 as a potential therapeutic target in MCL patients who are refractory to standard chemotherapy.